Telesna samopodoba slovenskih in francoskih osnovnošolcev z vidika gibalne aktivnosti - Pepevnik, Darko (Revija za elementarno izobraževanje, 2009)
The physical self-image of Slovene and French primary school pupils from the perspective of physical activities. In the introduction we present some current scientific findings about the physical self-conception of adolescents and how it is connected to the physical activities they are involved in. We carried out empirical research to find out to which degree Slovene and French adolescents evaluate their physical self-conception according to the physical activities they do. We were also interested in the relationship between physical activity and the extent of physical self-conception, and between physical activity and physical self-conception as a whole. The research is based on a sample of 11 to 15-year-old pupils (n = 1031) from urban and rural public schools in Slovenia (n = 566) and France (n = 465). We observed the difference among pupils according to their physical activity and the country they live in. We used a questionnaire that was based on the Physical Self-Inventory questionnaire (short form) designed by French authors. We were able to determine that Slovene pupils are physically more active than their French peers and that the pupils who are more physically active have a more positive physical self-conception. There is a low level of positive connections that were statistically distinctive between physical activity and self-conception. Our deductions indicate that there are no differences in the evaluation of physical self-conception regarding the country pupils live in. The general findings of our research indicate that most adolescents overrate themselves in the case of sports competence, physical appearance, physical self-conception, general self-conception and physical self-conception as a whole. The results of the research display a correlation between physical activity and the physical self-conception of adolescents. These findings confirm that it will be necessary to find and offer each individual a proper activity and to stimulate them in a way that would make this activity a part of their lifestyle.